2016
DOI: 10.18410/jebmh/2016/1159
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pretreatment With Magnesium Sulphate on Succinylcholineinduced Fasciculations and Myalgia

Abstract: BACKGROUNDSuccinylcholine, a depolarising muscle relaxant possesses a unique property of rapid onset and short duration of action, but is accompanied by side effects such as fasciculations and myalgia. A prospective randomised-controlled trial was designed to assess the effect of a combination of magnesium sulphate with propofol for induction of anaesthesia on succinylcholine-induced fasciculations and myalgia. MATERIALS AND METHODS60 adult patients of ASA status I and II of both sexes for elective surgery und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…In the present study, the preventive administration of magnesium sulfate in group B reduced the severity of fasciculation following the injection of succinylcholine. Further, other studies confirmed the findings of the present study regarding the positive and beneficial effects of the prophylactic administration of magnesium sulfate on fasciculation control (26)(27)(28). It seems that magnesium sulfate prevents severe fasciculation reactions by inhibiting acetylcholine secretion after the injection of succinylcholine.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the preventive administration of magnesium sulfate in group B reduced the severity of fasciculation following the injection of succinylcholine. Further, other studies confirmed the findings of the present study regarding the positive and beneficial effects of the prophylactic administration of magnesium sulfate on fasciculation control (26)(27)(28). It seems that magnesium sulfate prevents severe fasciculation reactions by inhibiting acetylcholine secretion after the injection of succinylcholine.…”
Section: Discussionsupporting
confidence: 92%